2012
DOI: 10.7314/apjcp.2012.13.2.693
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Profile of Breast Cancer Patients in Pakistan: Ten Years Data of a Local Cancer Hospital

Abstract: Breast cancer is the most frequent cancer of women worldwide, with considerable geographic and racial/ ethnic variation. Data are generally derived from population based cancer registries in the developed countries but hospital data are the most reliable source in the developing countries. Ten years data from 1st Jan 2000 to 31st Dec 2009 of a cancer hospital in Pakistan were here analyzed by descriptive statistics to evaluate the clinicopathologic profile of local breast cancer patients. Among 28,740 cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…The findings of the present study in consistent with other studies (Fouladi et al, 2012;Kadivar et al, 2012;Khokher et al, 2012;Afsharfard et al, 2013;Kotepui and Chupeerach, 2013) demonstrated that ductal carcinoma was the most prevalent malignancy in both menopausal and non-menopausal women (97% and 86.2%, respectively) and the rate of malignant masses was higher in menopausal women. This can be justified by the fact that the menopausal women's mean age is normally high and above 50-year-old ages are directly associated with the incidence of breast malignancies in women (Otu, 1990;Jemal et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present study in consistent with other studies (Fouladi et al, 2012;Kadivar et al, 2012;Khokher et al, 2012;Afsharfard et al, 2013;Kotepui and Chupeerach, 2013) demonstrated that ductal carcinoma was the most prevalent malignancy in both menopausal and non-menopausal women (97% and 86.2%, respectively) and the rate of malignant masses was higher in menopausal women. This can be justified by the fact that the menopausal women's mean age is normally high and above 50-year-old ages are directly associated with the incidence of breast malignancies in women (Otu, 1990;Jemal et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The knowledge of breast cancer symptoms and practice of breast self examination is inadequate among women living in the developing countries (Ahmed et al, 2006;Karayurt et al, 2008;Kumar et al, 2009;Khokher et al, 2012;Radi 2013;Ranasinghe et al, 2013). However there is evidence of significant improvement with the educational and awareness activities (Gupta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is a developing country with limited resources and has the highest incidence of breast cancer among the Asian countries, the ASR being 69.1 per 100,000 averaged over the years 1998-2002(Bhurgri et al, 2006. Breast cancer in this region is Samina Khokher 1 *, Muhammad Usman Qureshi 2& , Warda Fatima 3 , Saqib Mahmood 4 , Afaf Saleem 5 characterized by aggressive disease affecting younger age women with late stage presentations (Naeem et al, 2008;Khokher et al, 2012). Awareness campaign through public health education has the potential of raising the knowledge and awareness level of the women for early detection of disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancers are the most risk diseases which threaten our health at present, and there is rare indicator for early diagnosis. Breast and ovarian cancers are the most two frequent cancers of women worldwide, and the most lethal gynecological malignancy worldwide (Yip et al, 2006;Yip & Anderson, 2007;Gao et al, 2009;Khokher et al, 2012;Zhang et al, 2012). Early diagnosis and better prognosis of breast and ovarian cancers is still a challenge, and genetic factors have established a role in pathogenesis of breast and ovarian cancers (Yip et al, 2009;Gao et al, 2012;Jeschke et al, 2012;.…”
Section: Relationship Between the Prohibitin 3' Untranslated Region Cmentioning
confidence: 99%